OverMesh network-centric computing. - Vicente, John (IEEE Communications magazine)
The communications industry significantly lags behind the personal computing industry in terms of empowering the end user to innovate, as fundamental architectural shifts have yet to occur to push intelligence to the network edge. The decentralization of the telecommunication system to the edge of today's hierarchically formed networks is inevitable with the emergence of key wireless technologies and the proliferation of mobile computing devices and more prevailing usage models. This article envisions a decentralized communication system formed of wireless mesh networks and a highly virtualized, converged computing and communications node-based architecture with emergent management capabilities. We propose to embed the user inside the network to freely associate services and resources such as computing, storage, and bandwidth to rapidly advance network innovation - network-centric computing. This article proposes a novel direction and vision for network-centric computing, expands upon our research, and presents the OverMesh platform from which we have begun work to instantiate this vision. Finally, we expect this new envisioned network to coexist with today's Internet infrastructure and enable a new generation of applications and usage models.